2004
DOI: 10.1248/bpb.27.2042
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Interactions between Functional Foods or Dietary Supplements and Medicines. III. Effects of Ginkgo biloba Leaf Extract on the Pharmacokinetics of Nifedipine in Rats

Abstract: Standardized Ginkgo biloba leaf extract (GBE) is a widely used dietary supplement for the treatment or prevention of Alzheimer's disease, failing memory, age-related dementias, etc. in Japan as well as the United State, and now a phytomedicine in many countries in Europe.1) GBE consists of many flavonoid glycosides and various unique diterpenes such as ginkgolides, which are potent inhibitors of platelet activating factor.1) It is highly likely that GBE is used in combination with various medicines by many pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…This study demonstrated that pretreatment of GBE increased clearance of theophylline in rats by increasing CYP1A2 metabolic activity. Yoshioka et al (2004a) investigated the effects of GBE in rats on the pharmacokinetics of nifedipine (a calcium channel blocker) which is a typical probe of CYP3A, but not a substrate of the P-gp. These results suggest that the concomitant oral use of GBE and nifedipine in rats appeared to reduce the first-pass metabolism of the drug by inhibiting CYP3A, but not P-gp.…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…This study demonstrated that pretreatment of GBE increased clearance of theophylline in rats by increasing CYP1A2 metabolic activity. Yoshioka et al (2004a) investigated the effects of GBE in rats on the pharmacokinetics of nifedipine (a calcium channel blocker) which is a typical probe of CYP3A, but not a substrate of the P-gp. These results suggest that the concomitant oral use of GBE and nifedipine in rats appeared to reduce the first-pass metabolism of the drug by inhibiting CYP3A, but not P-gp.…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…In fact, available data for GBE effects on cytochrome P450 activity in vitro and in vivo from animal and human studies is inconsistent. In vitro studies in rat liver microsomes showed inhibitory effects of GBE on some CYPs [1012], whereas both inhibition [13, 14] and induction [15–17] was reported for in vivo studies. In vitro experiments carried out in human liver microsomes suggested that GBE weakly inhibits human CYP enzymes, e.g., CYP1A2 and CYP3A [18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of TCM in composition constituents [3], which usually interferes with the determination of target compounds, developing an efficient and accurate determination method is always at the cost of running time in chromatographic analysis or depends on optimal sample prepared method. To date, various analytical techniques have been developed to determine constituents in TCM; HPLC coupled with UV detection is by far the most commonly adopted method due to its efficiency and accuracy [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%